2021
DOI: 10.1136/jitc-2021-002989
|View full text |Cite
|
Sign up to set email alerts
|

Real-world performance of blood-based proteomic profiling in first-line immunotherapy treatment in advanced stage non-small cell lung cancer

Abstract: PurposeImmune checkpoint inhibition (ICI) therapy has improved patient outcomes in advanced non-small cell lung cancer (NSCLC), but better biomarkers are needed. A clinically validated, blood-based proteomic test, or host immune classifier (HIC), was assessed for its ability to predict ICI therapy outcomes in this real-world, prospectively designed, observational study.Materials and methodsThe prospectively designed, observational registry study INSIGHT (Clinical Effectiveness Assessment of VeriStrat® Testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Our model analyzes a large set of proteomic biomarkers, termed RAPs, that collectively provide a robust prediction of treatment benefit. Using supervised computational models to analyze omic-level data, we and others have previously identified blood-based signatures predictive of ICI outcomes [11][12][13][14] . However, successful validation can be challenging due to several intrinsic limitations, including overfitting and inter-and intra-patient heterogeneity, while large sample sizes are necessary to achieve acceptable model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Our model analyzes a large set of proteomic biomarkers, termed RAPs, that collectively provide a robust prediction of treatment benefit. Using supervised computational models to analyze omic-level data, we and others have previously identified blood-based signatures predictive of ICI outcomes [11][12][13][14] . However, successful validation can be challenging due to several intrinsic limitations, including overfitting and inter-and intra-patient heterogeneity, while large sample sizes are necessary to achieve acceptable model performance.…”
Section: Discussionmentioning
confidence: 99%
“…described a blood-based host immune classifier (HIC) proteomic testing to classify NSCLC patients. HIC classification could predict survival with ICI-based therapy and select NSCLC patients who were responding to immunotherapy ( 94 ). Zhang et al.…”
Section: Cutting-edge Progress In Biomarker Explorationmentioning
confidence: 99%
“…44 45 More recent analyses have shown that HIC is also predictive, when considering immunotherapy alone or in combination with chemotherapy for patients with high PD-L1 status. 46 …”
Section: Current State Of Serum Proteomic Tests In Clinicmentioning
confidence: 99%